RELEVANSI ANTARA PROGRAM STUDI KEAHLIAN TEKNIK BANGUNAN DENGAN PEKERJAAN YANG DIPEROLEH LULUSAN SMK DI KABUPATEN LOMBOK BARAT - Baiq Rina Amalia Safitri; Haris A. Syafrudie; Sutrisno Sutrisno (Universitas Pendidikan Mandalika, 2013)
The purpose of the study is to know the information of the relevancy of civil engineering expertise study program on occupation obtained by the graduates of Secondary Vocational School in Lombok Barat regency. Data was gathered by using questionnaire analysis from 50 graduates of civil engineering expertise study program of 2007 and 2008 academic years and data was analyzed by using descriptive technique. The findings show that (1) the relevancy of occupation, expertise, and knowledge for steel construction technique has means of 12.20, 8.92 and 10.37 respectively and those three belong to irrelevant category; (2) the relevancy of occupation, expertise, and knowledge for wood construction technique has means of 38.86, 28.00, and 32.41 respectively, and those three belong to irrelevant category; (3) the relevancy of occupation, expertise, and knowledge for stone and concrete construction technique has means of 70.73, 54.88, and 65.85 and those three belong to relevant category; (4) the relevancy of occupation, expertise, and knowledge for construction sketch has means of 82.04, 65.32, and 81.15, and those three belong to relevant category.